Nanostructure evolution of silica aerogels under rapid heating from 600 °C to 1300 °C via in-situ TEM observation. Issue 8 (1st June 2020) - Cai, Huafei; Jiang, Yonggang; Feng, Jian; Chen, Qu; Zhang, Sizhao; Li, Liangjun; Feng, Junzong
Abstract: Silica aerogel is a typical nanoporous material exhibiting excellent thermal insulation property, and its nanostructure change at high temperature has attracted extensive attention. However, there is a lack of real-time research on the nanostructure evolution of silica aerogel under rapid heating. Here, silica aerogel was rapidly heated and imaged via an in-situ heating TEM to characterize the nanostructure evolution of from 600 °C to 1300 °C. After rapid heating at different temperatures, the silica aerogels were characterized by SEM, BET, TG-DSC, XRD and FT-IR. The nanostructure evolution of the aerogels can be divided into three temperature stages and experimental strategies for inhibiting aerogel shrinkage at high temperature can be provided. In stage Ⅰ (600 °C–1000 °C), the shrinkage of the silica aerogels occurred during the initial time of the heating process (within 2 h), and then the structure of silica aerogel became stable. The shrinkage of silica aerogels is primarily caused by the fusion of secondary particles, and increasing the secondary silica aerogel particle size may contribute to reducing the aerogel shrinkage. In stage Ⅱ (1100 °C), the aerogel shrinkage can be observed all the time with the heating process continues, and finally closed to the dense state. The shrinkage of silica aerogels is caused by the fusion of secondary particles and the macropore collapse, increasing the particle size and reducing the macropore content may slow down aerogel shrinkage. In stage Ⅲ (1200 °C–1300 °C), the aerogel will shrink rapidly and reach a dense state in a very short time (within 0.5 h). The shrinkage of silica aerogels is caused by the rapid pore collapse and the rapid fusion and shrinkage of the secondary particles of the aerogel, and pure silica aerogels cannot be used at this temperature. Highlights: The SiO2 aerogels nanostructure evolution under rapid heating condition was studied. The real time nanostructure changes were observed via an in-situ heating TEM. Secondary particles fusion and macropore collapse are key factors for the evolution. The strategies for inhibiting silica aerogel shrinkage at high temperature were provided.